Model Institusiometrika untuk Perencanaan Pendidikan - Sapto J. Poerwowidagdo (Universitas Negeri Malang, 2016)
Institutiometric model is designed to support the education institution in optimizing its resource management, and its resource development.The number of enrollment, the number of student body, the number of graduates, the budget, and the lecturers are the proxy variables for the education resources. These basic variables are processed to become index variables, created variables, and attained variables. These variables are used to build an institutiometric model, based on a Markov chain model, as a predictive model for the educational planning. It is expected that this model can be applied for the educational planning in both private and state higher education institu-tions, or in other educational institutions.